Management of human talent and job skills of health personnel in a hospital in Peru - Karen Sthephanie Gómez Guadalupe; Davis Alberto Mejía Pinedo; Carlos Diez Morales; Ericcson Felix Castillo Saavedra; Cecilia Elizabeth Reyes Alfaro; Cintia Rosales Márquez (Medisur)
Foundation: Human talent management and job competencies are crucial aspects in the healthcare field, as they directly influence the quality of care provided to patients. The interrelationship between these variables is fundamental to ensure operational efficiency and achieve institutional objectives. Objective: To determine the relationship between human talent management and job competencies in the healthcare staff of a hospital in Peru. Methods: A simple correlational design was used with a sample of 100 participants from the healthcare staff. Two questionnaires were applied: one on human talent management (28 items) and another on job competencies (20 items). The data were analyzed using descriptive statistics, and the reliability of the instruments was assessed with Cronbach's Alpha coefficient. Results: There is a significant correlation between human talent management and job competencies (Rho=0.816). The dimensions of recruitment, selection, training, reward, and performance evaluation also showed specific correlations with job competencies, with coefficients ranging from 0.876 to 0.978. The questionnaires presented high reliability (Cronbach's Alpha: 0.980 and 0.973). Conclusions: Human talent management and job competencies are strongly related in the healthcare staff of the studied hospital, highlighting the importance of effective strategies to improve the quality of care.